IMPLEMENTASI COLLABORATIVE GOVERNANCE DI INDONESIA - Ticha Nurda Fitri; M. Fachri Adnan; Syamsir Syamsir (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Collaborative Governance is a process that involves various stakeholders (parties) who are bound to carry the interests of each agency in achieving common goals. This study aims to find out how the development of collaborative governance in Indonesia is seen from the theoretical and practical settings and how the solutions are solved. With the systematic approach to Literature Review in journals that have been published from 2011 to 2021, the results show that HR research currently focuses on two topics and trends: limited capabilities and resources. The method that is often used in collaborative governance research in Indonesia is a qualitative approach of 80%, a quantitative approach of 15% and a mix method approach of 5%. The cause of the problems in improving the implementation of collaborative governance in Indonesia, governance demands the implementation of the rules of public information disclosure. Justice, transparency, participation, and accountability are prerequisites for the creation of good governance and free from corruption, collusion and nepotism. The solution given to answer the problem of the low implementation of collaborative governance in Indonesia is the process of building trust between stakeholders is the starting point for Collaborative Governance where the process is not only about negotiation but also about building trust among stakeholders and must be equitable that focuses on network members embedded a sense of mutuality. trust each other and the actors have done Trust Building/Building Trust from Collaborative Governance.Keywords: Systematics Literature Review collaborative governance.